IMPLEMENTASI PERATURAN MENTERI NEGARA LINGKUNGAN HIDUP NO 13 TAHUN 2012 TENTANG PEDOMAN PELAKSANAAN REDUCE, REUSE DAN RECYCLE MELALUI BANK SAMPAH DI KOTA PEKANBARU - Hendri, Resyia; R.F.S, Harapan Tua (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The population in Pekan Baru has increased rapidly which cause of environment problem appear, namely the management of garbage. One of policies in solving trash problem is the regulation of environment Minister no 13 year 2012 on the implementation guidance of Reduce, Reuse, and Recycle through garbage Bank. The garbage Bank is the method to build the system of garbage management to provide monetary punishment to the people who participate in sorting and collecting the garbage. The fact, garbage Bank is still any improvement yet to increase the citizen awareness in management of garbage. The purpose of this research is to know and to describe about implementation and the factors that influence and also obstructions on the garbage Bank program in Pekanbaru. This research used implementation theory in accordance with Donald S. Van Meter and Carl E. Van Horm namely : (1)standard and target policy (2)resources (3)characteristics of implementation agency (4)implementation disposition (5)communication among organization(6) social area, economy environment and politics. This research used qualitative method. In collecting data, the researcher used observation, interview, and documentation technique. The purposive of sampling technique was used in choosing interviewees. Interviewees in this research were department head of BLH Pekan Baru , division head of controlling damage and environment recovery BLH Pekanbaru, Manager of garbage Bank Dallang Collection sub-district of Tenayan Raya and society. The research findings indicate that the implementation of regulation of Minister of environment No.13 year 2012 about guidance of Reduce, Reuse, and Recycle through garbage Bank in Pekanbaru is not optimal yet, there are many problems are appeared such as lack of aware of society about garbage Bank program, lack of resources to be volunteer, coordination and communication not  effectively and social environment policy is not support  in implementing this policy. This things resulted the goal destination in implementation of policy has not reached totally. Key Word : Implementation of policy, Garbage, Garbage bank